Beyond Energy Metabolism: Exploiting the Additional Roles of NAMPT for Cancer Therapy - Heske, Christine M. (Frontiers in Oncology, 2020)
Tumor cells have increased requirements for NAD+. Thus, many cancers exhibit an increased reliance on NAD+ production pathways. This dependence may be exploited therapeutically through pharmacological targeting of NAMPT, the rate-limiting enzyme in the NAD+ salvage pathway. Despite promising preclinical data using NAMPT inhibitors in cancer models, early NAMPT inhibitors showed limited efficacy in several early phase clinical trials, necessitating the identification of strategies, such as drug combinations, to enhance their efficacy. While the effect of NAMPT inhibitors on impairment of energy metabolism in cancer cells has been well described, more recent insights have uncovered a number of additional targetable cellular processes that are impacted by inhibition of NAMPT. These include sirtuin function, DNA repair machinery, redox homeostasis, molecular signaling, cellular stemness, and immune processes. This review highlights the recent findings describing the effects of NAMPT inhibitors on the non-metabolic functions of malignant cells, with a focus on how this information can be leveraged clinically. Combining NAMPT inhibitors with other therapies that target NAD+-dependent processes or selecting tumors with specific vulnerabilities that can be co-targeted with NAMPT inhibitors may represent opportunities to exploit the multiple functions of this enzyme for greater therapeutic benefit.